Impact of Corporate Governance Practices on Earnings Management Strategies - Arif, Muhammad; Qazi, Laila Taskeen; Atta ur Rahman (The Journal of Humanities & Social Sciences, 2024)
The study investigates the relationship between good corporate governance factors, including board size and board composition, which represent the number of non-executive directors, CEO and chairman duality with inflating or deflating income, known as earnings management. A set of 100 manufacturing companies listed on KSE has been investigated over four years (2019-2023) to analyze the intended relationship. Quality of corporate governance has been measured by allocating values to each variable, whereas earnings management is measured on the basis of discretionary accruals by using the Modified Cross Sectional Jones model. Results obtained through the weighted Least Square (WLS) Method of estimation point out a positive relation between the number of directors on board and discretionary accruals, a negative relation between board composition and earnings management, while duality of CEO shows a positive relationship with earnings management. The overall result of the study shows a significant impact of corporate governance practices on earnings management.